Development of Freeware-Mobile Application for Learning Electrical Installation in Vocational High Schools - Triantini, Dewi; Supriyadi, Edy; Abubakari, Mussa Saidi (DPTE FT UNY, 2025)
The study aims to design and develop a freeware application for electrical installation planning analysis. This research is categorized as development research, adopting the RAPID Application Development (RAD) model. The data collection process in this study involved a series of methods, including direct observation of the learning process, in-depth interviews with potential users, and the distribution of structured questionnaires to relevant respondents. The analysis of the collected data was carried out using a quantitative descriptive method, which aimed to describe and interpret numerical data related to the performance and acceptance of the developed application. The overall results of this study indicate that the designed and developed freeware application, as a learning media for electrical installation planning analysis, demonstrates highly satisfactory performance and falls into the